Factors Influencing Health-Related Practices Among Hispanic Parents: A Formative Study to Inform Childhood Obesity Prevention - Ana Paola Campos; Julian Robles; Katherine E. Matthes; Maihan B. Vu; Ramine C. Alexander; Rachel W. Goode (Children)
Background: Childhood obesity disproportionately affects Hispanic families in the U.S. Although parenting practices and interventions appear to be viable approaches to lower the risk of childhood obesity, there is limited information on which parenting practices would be relevant and culturally appropriate for Hispanic families. This study aimed to document the health-related factors that impact Hispanic parenting practices to inform evidence-based parenting interventions to improve child health outcomes and reduce the risk of childhood obesity. Methods: We conducted cross-sectional, formative research guided by the COREQ checklist. Hispanic parents of elementary school-aged children were recruited using purposive and snowball sampling. Eligible parents completed a brief sociodemographic survey, the Comprehensive Feeding Practices Questionnaire (CFPQ), and an individual semi-structured interview. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using a coding-based thematic approach. Results: Seventeen parents (88.2% female) participated in the study, and the majority reported Spanish as their preferred language (70.6%). According to parent-reported data, the children’s (52.9% female) mean age was 8.4 ± 1.5 years, and over half were classified as having overweight or obesity. The CFPQ analysis indicated that parents scored highest on subscales related to encouraging healthy eating and eating variety, a finding that was reinforced by interview data. Qualitative analysis identified four key themes: 1. parenting roles, routines, and strategies for promoting culturally appropriate and healthy meals; 2. beliefs of children’s health and weight; 3. beliefs on physical activity and screen time; and 4. environmental and social factors affecting access to healthy food and physical activity. Conclusions: Both quantitative and qualitative results emphasize that parents engage in healthy eating guidance and eating variety and are aware of the factors that impact parenting practices and their children’s health. To improve child health outcomes and reduce the risk of childhood obesity among Hispanic families, parenting interventions need to be culturally responsive and address the factors that influence parenting practices. The findings from this study highlight four key areas to prioritize when designing or adapting parenting interventions to lower the risk of childhood obesity among Hispanic families.